Resin sheet, heat dissipation member, laminate, and resin composition
The resin sheet with a high volume ratio of single crystalline fillers addresses the issue of resin and filler separation in heat dissipation sheets, ensuring uniform distribution and improved thermal conductivity and reliability.
Patent Information
- Application Number
- JP2023156222
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
In heat dissipation sheets for boards with built-in parts, the separation of resin and thermally conductive filler occurs during lamination, leading to uneven filler distribution and reduced reliability due to differences in linear expansion coefficients.
A resin sheet is developed with a thermally conductive filler composition that includes single crystalline fillers, such as α-alumina, at a volume ratio of at least 12%, along with other fillers, to suppress separation and ensure uniform distribution.
The solution effectively suppresses the separation of resin and thermally conductive filler, maintaining uniform filler distribution and enhancing the reliability and thermal conductivity of the heat dissipation sheet.
Smart Images

Figure 2025047624000010 
Figure 2025047624000011 
Figure 2025047624000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin sheet, a heat dissipation member, a laminate, and a resin composition. [Background technology]
[0002] Thermally conductive resin compositions and resin sheets are widely used as heat dissipation materials, and various kinds of them have been proposed. For example, Patent Document 1 discloses an epoxy resin composition containing a liquid epoxy resin (A), a curing agent (B), and an inorganic filler (C), in which the inorganic filler (C) has a particle size (D50) corresponding to 50% of the cumulative particle size distribution on a volume basis of 0.1 μm or more and 0.5 μm or less, and contains α-alumina with an α-crystallization rate of 80% or more.
[0003] Patent Document 2 discloses a semiconductor adhesive used to seal a connection in a semiconductor device having a connection structure in which connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other, and / or a connection structure in which connection portions of a plurality of semiconductor chips are electrically connected to each other. Patent Document 2 discloses that the semiconductor adhesive contains a curable resin component and an alumina filler having an average particle size of 15 μm or less, the content of the alumina filler is 35 to 75 mass% based on the total amount of the semiconductor adhesive, and the thermal conductivity of the semiconductor adhesive after curing is 0.5 to 1.5 W / mK.
[0004] Patent Document 3 discloses an insulating curable resin composition for printed wiring boards, which contains spherical aluminum oxide particles having a thermal conductivity of 15 W / m K or more and a curable resin composition, in which the volume occupancy of the aluminum oxide particles is 60 vol % or more of the total volume of a cured product of the resin composition for printed wiring boards, and the cured product has a thermal conductivity of 2 W / m K or more.
[0005] Patent Document 4 discloses a resin composition comprising a liquid epoxy resin, a curing agent, and an alumina filler surface-treated with a silane coupling agent having a specific structure. The resin composition also discloses a resin composition in which the content of the alumina filler surface-treated with the silane coupling agent having the specific structure is 45 to 77 parts by mass relative to 100 parts by mass of the total mass of all components of the resin composition.
[0006] Patent Document 5 also discloses a resin composition for application to the underfill sealing destination, which is applied to a circuit board, a semiconductor chip is mounted thereon, and then the composition is cured by heat conduction caused by heating from above the semiconductor chip. Patent Document 5 discloses a liquid epoxy resin composition for application to the underfill sealing destination, which contains, as the resin composition, an epoxy resin and a curing agent, as an inorganic filler, spherical aluminum oxide having a maximum particle size of 0.5 μm to 15 μm, in a volume content of 5 vol% to 50 vol% relative to the entire composition. Furthermore, the liquid epoxy resin composition also discloses one in which the volume content of the spherical aluminum oxide is 15 vol% to 45 vol%.
[0007] Patent Document 6 discloses an insulating curable resin composition for printed wiring boards, which comprises spherical aluminum oxide particles having a thermal conductivity of 15 W / m·K or more and a curable resin composition, in which the volume occupancy of the aluminum oxide particles is 60% by volume or more relative to the total volume of the cured product, and the cured product has a thermal conductivity of 2 W / m·K or more. Patent Document 6 discloses that the curable resin composition is a thermosetting resin composition, and contains an epoxy compound and / or an oxetane compound, and a curing agent and / or a curing catalyst, etc. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent Publication No. 2022-060084 [Patent Document 2] International Publication No. 2021 / 200553 [Patent Document 3] International Publication No. 2007 / 020793 [Patent Document 4] Patent No. 6405209 [Patent Document 5] Patent No. 4966221 [Patent Document 6] Patent No. 4920929 Summary of the Invention [Problem to be solved by the invention]
[0009] In recent years, with the miniaturization and high performance of electrical devices, component-embedded boards with various components built inside them have been attracting attention. In component-embedded boards, the built-in components can generate heat, so a sheet-shaped heat dissipation material with a large amount of heat dissipation filler packed into the resin is required. Generally, heat dissipation sheets are laminated with a substrate or the like and molded by heat pressing. However, when a heat dissipation sheet is laminated on a substrate in a thermally molten state, the filler and the resin may separate, particularly in places such as depressions in the substrate where the molten resin flows first and the filler is difficult to fill, causing the filler to become unevenly distributed in certain places. In such cases, the linear expansion coefficient differs between the places where the filler is unevenly distributed and other places, which can reduce the reliability of the heat dissipation sheet. Furthermore, in recent years, the number of fine grooves has increased due to the refinement of substrates, and in order to address this, the use of small particle diameter heat dissipating fillers has been considered. However, the use of small particle diameter heat dissipating fillers makes the above-mentioned separation more likely to occur.
[0010] Therefore, an object of the present invention is to provide a resin sheet in which separation of the resin and the thermally conductive filler is suppressed. [Means for solving the problem]
[0011] As a result of extensive research, the inventors have found that the above-mentioned problems can be solved by blending a certain proportion or more of a single-crystalline filler as a thermally conductive filler, even when a small particle size filler is highly loaded. That is, the present invention provides the following [1] to [8].
[0012] [1] A resin sheet comprising a resin and a thermally conductive filler, the resin sheet satisfying the following conditions (1) to (3): (1) The content of the thermally conductive filler is 50% by volume or more and 80% by volume or less based on the total volume of the resin sheet. (2) The average particle size of the thermally conductive filler is from 2 μm to 8 μm. (3) The thermally conductive filler contains a monocrystalline filler in an amount of 12% by volume or more based on the total amount of the thermally conductive filler. [2] The resin sheet according to [1], wherein the resin is a thermosetting resin. [3] The resin sheet according to [2], wherein the thermosetting resin contains an epoxy resin. [4] The resin sheet according to any one of [1] to [3], wherein the monocrystalline filler contains α-alumina. [5] The resin sheet according to any one of [1] to [4], wherein the thermally conductive filler is surface-treated with a silane coupling agent, or the resin sheet contains a dispersing agent. [6] A heat dissipation member formed from the resin sheet according to any one of [1] to [5]. [7] A laminate comprising a support and the resin sheet according to any one of [1] to [5] provided on the support. [8] A resin composition comprising a resin and a thermally conductive filler, the resin composition satisfying the following conditions (1) to (3): (1) The content of the thermally conductive filler is 50% by volume or more and 80% by volume or less based on the total volume of the resin composition. (2) The average particle size of the thermally conductive filler is from 2 μm to 8 μm. (3) The thermally conductive filler contains a monocrystalline filler in an amount of 12% by volume or more based on the total amount of the thermally conductive filler. Effect of the Invention
[0013] According to the present invention, it is possible to provide a resin sheet in which separation of the resin and the thermally conductive filler is suppressed. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view showing an example of a semiconductor chip package. [Diagram 2] FIG. 2 is a schematic diagram showing a process of laminating a resin sheet onto a copper plate in an evaluation of embeddability. [Diagram 3] FIG. 11 is a schematic cross-sectional view of a through hole divided into five regions after components of a resin sheet have flowed in. [Figure 4] FIG. 2 is a schematic diagram showing a method for evaluating sheet properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Resin sheet] Hereinafter, the present invention will be described with reference to embodiments. The resin sheet of the present invention contains a resin and a thermally conductive filler.
[0016] (Thermal conductive filler) The resin sheet of the present invention contains a thermally conductive filler, and contains a single-crystalline filler as the thermally conductive filler in an amount of 12% by volume or more based on the total amount of the thermally conductive filler. Since the surface of the single-crystalline filler is smooth, by setting the ratio of the single-crystalline filler to a certain level or more in the entire thermally conductive filler, it becomes easier to suppress the occurrence of friction between fillers and the decrease in the fluidity of the thermally conductive filler due to friction between fillers, and separation between the resin and the thermally conductive filler can be suppressed. On the other hand, if the content of the single-crystalline filler is less than 12% by volume based on the total amount of the resin sheet, it becomes difficult to suppress the above separation. From the above viewpoint, the content of the single-crystalline filler is preferably 15% by volume or more, more preferably 30% by volume or more, and even more preferably 50% by volume or more.
[0017] From the viewpoint of suppressing separation between the resin and the thermally conductive filler, the more the content of the single-crystalline filler is, the better, and it is sufficient that the content is 100% by volume or less based on the total amount of the thermally conductive filler, but as described later, a thermally conductive filler other than the single-crystalline filler may be contained within a range that can suppress separation between the resin and the thermally conductive filler. In that case, the content of the single-crystalline filler is, for example, 95% by volume or less, preferably 90% by volume or less, more preferably 85% by volume or less, and even more preferably 80% by volume or less based on the total amount of the thermally conductive filler. Whether or not the thermally conductive filler is a single crystal filler can be identified by, for example, X-ray analysis.
[0018] The content of the thermally conductive filler in the resin sheet of the present invention is 50% by volume or more and 80% by volume or less based on the total volume of the resin sheet. If the content of the thermally conductive filler is less than 50% by volume based on the total volume of the resin sheet, the viscosity of the entire resin sheet decreases, and for example, when the resin sheet is used for a component-embedded board application, the resin may enter narrow gaps such as grooves between components first, and separation between the resin and the filler may occur. There is also a risk of the thermal conductivity being reduced. On the other hand, if the content of the thermally conductive filler exceeds 80% by volume based on the total volume of the resin sheet, friction between the thermally conductive fillers is likely to occur, and separation between the resin and the filler may occur. Furthermore, the sheet properties of the resin sheet may be reduced, and the handling properties may be reduced. Considering the above points, the content of the thermally conductive filler is preferably 52 vol % or more and 77 vol % or less, and more preferably 55 vol % or more and 73 vol % or less.
[0019] The thermally conductive filler contained in the resin sheet of the present invention has an average particle size of 2 μm or more and 8 μm or less. If the average particle size of the thermally conductive filler is less than 2 μm, the surface area of the thermally conductive filler becomes too large, causing friction of the thermally conductive filler, making it difficult for the thermally conductive filler to flow, and there is a risk of separation between the resin and the thermally conductive filler. If the average particle size of the thermally conductive filler exceeds 8 μm, it becomes difficult for the thermally conductive filler to enter a narrow gap, which may cause separation between the resin and the thermally conductive filler. From the above viewpoints, the average particle size of the thermally conductive filler is preferably 2.5 μm or more and 7.9 μm or less, more preferably 2.8 μm or more and 7.8 μm or less.
[0020] The average particle size mentioned above refers to the average particle size of all the thermally conductive fillers contained in the resin sheet. The average particle size of the thermally conductive filler can be measured by observation with an electron microscope or the like. More specifically, for example, the particle sizes of 100 arbitrary thermally conductive fillers can be measured using an electron microscope or an optical microscope, and the average value (arithmetic mean value) can be regarded as the average particle size. For example, when the thermally conductive filler is an agglomerated particle, the average particle size of the agglomerated particle may be within the above range.
[0021] Examples of the single crystalline filler include alumina and diamond. The single crystalline filler may be used alone or in combination of two or more. Among these, at least one selected from alumina and diamond is preferred, alumina is preferred, and α-alumina is more preferred. When using α-alumina as the single crystalline filler, α-alumina may be used alone as the single crystalline filler, or other single crystalline fillers such as diamond may be used in addition to α-alumina. As-grown diamond can be used as a single-crystalline filler. As-grown diamond is a single-crystalline particle that maintains the shape of the crystalline diamond obtained by high-temperature and high-pressure method without crushing.
[0022] The thermally conductive filler may include a thermally conductive filler other than the monocrystalline filler. Examples of the thermally conductive filler other than the monocrystalline filler include crushed filler, polycrystalline filler, and non-crystalline filler. The crushed filler is a filler obtained by crushing a monocrystalline filler, a polycrystalline filler, or a non-crystalline filler. Specific examples of the thermally conductive filler include carbides, nitrides, oxides, hydroxides, and carbon-based materials. Examples of carbides include silicon carbide, boron carbide, aluminum carbide, titanium carbide, and tungsten carbide. Examples of nitrides include silicon nitride, boron nitride, aluminum nitride, gallium nitride, chromium nitride, tungsten nitride, magnesium nitride, molybdenum nitride, and lithium nitride. Examples of oxides include zinc oxide, iron oxide, boehmite, and aluminum oxide other than the monocrystalline filler, such as alumina, metal oxides such as magnesium oxide, titanium oxide, cerium oxide, and zirconium oxide, and silicon oxide (silica). Examples of hydroxides include metal hydroxides such as aluminum hydroxide, calcium hydroxide, and magnesium hydroxide. Examples of carbon-based materials include diamond other than the monocrystalline filler, carbon black, graphite, graphene, fullerene, carbon nanotubes, and carbon nanofibers. Examples of diamond other than the monocrystalline filler include crushed diamond obtained by crushing as-grown diamond. Preferred examples of the thermally conductive filler other than the single crystal filler include aluminum oxide, aluminum nitride, diamond, and silicon carbide. The thermally conductive fillers other than the monocrystalline filler may be used alone or in combination of two or more kinds.
[0023] From the viewpoint of effectively enhancing the heat dissipation property of the resin sheet, it is preferable to use two or more types of thermally conductive fillers having different average particle sizes in combination, and it is more preferable to use two types of thermally conductive fillers having different average particle sizes in combination. The thermally conductive filler preferably includes, for example, a small-diameter thermally conductive filler having an average particle size of 0.05 μm or more and less than 1.5 μm, and a large-diameter thermally conductive filler having an average particle size of 1.5 μm or more and less than 10 μm. The average particle size of the small-diameter thermally conductive filler is preferably 0.1 μm or more and 1 μm or less, and the average particle size of the large-diameter thermally conductive filler is preferably 2 μm or more and 8 μm or less. When a small particle size thermally conductive filler and a large particle size thermally conductive filler are used in combination, the mass of the large particle size thermally conductive filler relative to the mass of the small particle size thermally conductive filler (amount of large particle size thermally conductive filler / amount of small particle size thermally conductive filler) is, for example, 0.5 or more and 15 or less, preferably 1 or more and 10 or less, and more preferably 1.5 or more and 8 or less. Incidentally, the resin sheet can be determined to contain two or more types of thermally conductive fillers having different average particle sizes when two or more peaks appear in the particle size distribution of the thermally conductive filler.
[0024] (resin) The resin contained in the resin sheet of the present invention is preferably a curable resin, more preferably a thermosetting resin. Examples of the thermosetting resin include amino resins such as urea resins and melamine resins, phenolic resins, thermosetting urethane resins, epoxy resins, silicone resins, phenoxy resins, thermosetting polyimide resins, aminoalkyd resins, benzoxazine resins, and bismaleimide resins. Among these, epoxy resins are preferred.
[0025] The epoxy resin may be, for example, a compound containing two or more epoxy groups in the molecule, and may have a weight average molecular weight of, for example, less than 10,000, preferably 5,000 or less. The weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) in terms of polystyrene. In gel permeation chromatography (GPC) measurements, tetrahydrofuran is preferably used as an eluent. However, when the molecular weight is a low molecular weight of 1000 or less, the weight average molecular weight may be calculated from the structural formula. In the resin sheet, the epoxy resin may react due to curing, but the weight average molecular weight refers to the weight average molecular weight of the epoxy resin before curing.
[0026] Specific examples of the epoxy resin include epoxy resins having a mesogen skeleton, such as styrene skeleton-containing epoxy resins, resorcinol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, biphenol type epoxy resins, phenoxy type epoxy resins, naphthalene type epoxy resins, phenylene ether type epoxy resins, fluorene type epoxy resins, phenol aralkyl type epoxy resins, naphthol aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, anthracene type epoxy resins, and biphenyl type epoxy resins, epoxy resins having an adamantane skeleton, epoxy resins having a tricyclodecane skeleton, and epoxy resins having a triazine nucleus in the skeleton, and glycidylamine type epoxy resins. Among the above, at least one selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, dicyclopentadiene type epoxy resin, and epoxy resin having a mesogenic skeleton is preferable, and at least one selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, and dicyclopentadiene type epoxy resin is more preferable.
[0027] The epoxy equivalent of the epoxy resin is not particularly limited, but is, for example, 100 g / eq or more and 1000 g / eq or less. The epoxy equivalent of the epoxy resin is preferably 120 g / eq or more, more preferably 140 g / eq or more, and is preferably 500 g / eq or less, more preferably 400 g / eq or less. The epoxy equivalent can be measured, for example, according to the method specified in JIS K 7236.
[0028] The resin may be a polymer having a weight average molecular weight of, for example, not less than 10000. By using a polymer, the sheet properties of the resin sheet can be easily improved. The polymer may be a thermosetting resin or a resin other than a thermosetting resin, but is preferably a thermosetting resin. The polymer may have a functional group such as an epoxy group or a hydroxyl group. The polymer is preferably used in combination with a thermosetting resin (hereinafter sometimes referred to as "resin (A)") having a weight average molecular weight of, for example, less than 10,000, and is particularly preferably used in combination with an epoxy resin as resin (A). The weight average molecular weight of resin (A) is preferably 5,000 or less.
[0029] Specific examples of polymers include phenoxy resin, polyester resin, polyether resin, polyamide resin, polyamideimide resin, polyimide resin, polyvinyl butyral resin, polyvinyl formaldehyde resin, polyhydroxypolyether resin, polystyrene resin, polycarbonate resin, butadiene resin, acrylonitrile-butadiene copolymer, acrylonitrile-butadiene-styrene resin, styrene-butadiene copolymer, etc. Among these, it is preferable to use phenoxy resin. Examples of the phenoxy resin include phenoxy resins having a skeleton such as a bisphenol A skeleton, a bisphenol F skeleton, a bisphenol S skeleton, a bisphenolacetophenone skeleton, a novolac skeleton, a biphenyl skeleton, a fluorene skeleton, a dicyclopentadiene skeleton, a norbornene skeleton, a naphthalene skeleton, an anthracene skeleton, an adamantane skeleton, a terpene skeleton, a trimethylcyclohexane skeleton, an imide skeleton, etc. The phenoxy resin may or may not have an epoxy group.
[0030] Commercially available examples of the phenoxy resin include "YP-50S", "YP55", and "YP70" (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), "JER1256", "JER4250", "JER4275", "YX6954BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7891BH30", and "YL7482" (all manufactured by Mitsubishi Chemical Corporation).
[0031] The weight average molecular weight of the polymer is not particularly limited, but is preferably 20,000 or more, more preferably 35,000 or more, and preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 70,000 or less.
[0032] In the resin sheet of the present invention, when a polymer is used, it is preferably used in combination with resin (A). When resin (A) and a polymer are used in combination, the mass ratio of resin (A) / polymer is not particularly limited, but is, for example, 0.1 to 10, preferably 0.2 to 8, more preferably 0.3 to 7, and even more preferably 0.2 to 8. The resin (A) and the polymer may be used alone or in combination of two or more kinds.
[0033] The content of resin (A) is, for example, 20 mass% or more and 80 mass% or less, preferably 30 mass% or more and 75 mass% or less, more preferably 35 mass% or more and 70 mass% or less, and even more preferably 40 mass% or more and 65 mass% or less, based on the total amount of components of the resin sheet excluding the thermally conductive filler. The total content of the resin (A) and the polymer is, for example, 20% by mass or more and 90% by mass or less, preferably 30% by mass or more and 85% by mass or less, more preferably 35% by mass or more and 80% by mass or less, and even more preferably 40% by mass or more and 75% by mass or less, based on the total amount of components of the resin sheet excluding the thermally conductive filler.
[0034] (hardening agent) The resin sheet of the present invention may contain a curing agent as necessary. The curing agent is preferably contained together with the thermosetting resin, and more preferably contained together with the epoxy resin. For example, when the resin sheet contains an epoxy resin, the curing agent preferably contains at least one selected from a curing agent having a triazine skeleton, a cyanate ester curing agent, a diamine curing agent, a phenolic curing agent, an amine curing agent, an acid anhydride curing agent, a mercaptan curing agent, and an imidazole curing agent. Among them, it is more preferable to contain at least one selected from a curing agent having a triazine skeleton, a cyanate ester curing agent, a diamine curing agent, and an acid anhydride curing agent. By using these as the curing agent, it becomes easier to impart excellent thermal conductivity to the resin sheet.
[0035] <Curing agent having a triazine skeleton> As the curing agent having a triazine skeleton, there can be mentioned a phenolic compound, an amine compound, a thiol compound, an imidazole compound, a phosphine compound, etc. having a triazine skeleton, among which a phenolic compound having a triazine skeleton is preferred.Moreover, as the curing agent having a triazine skeleton, a compound having an aminotriazine skeleton is more preferred.The curing agent having a triazine skeleton can easily improve thermal conductivity by increasing the alignment due to the triazine skeleton. Examples of the phenolic compound having a triazine skeleton include novolac-type phenolic compounds, and more specifically, novolac-type phenolic resins modified with melamine, benzoguanamine, etc. Examples of the phenolic compound having a triazine skeleton include "Phenolite (registered trademark) LA-7052", "Phenolite (registered trademark) LA-7054", "Phenolite (registered trademark) LA-7751", "Phenolite (registered trademark) LA-1356", and "Phenolite (registered trademark) LA-3018-50P" (all manufactured by DIC Corporation). The curing agent having a triazine skeleton may be used alone or in combination of two or more kinds.
[0036] <Cyanate ester hardener> Cyanate ester curing agents are compounds that have a cyanate ester group (-OCN). Some of the cyanate ester groups are trimerized during curing to form a triazine skeleton, which, together with the resin, forms a highly ordered molecular structure after curing, making it easier to improve thermal conductivity. In addition, the cyanate ester curing agent preferably has two or more cyanate ester groups in one molecule from the viewpoint of improving the curability. The cyanate ester curing agent preferably has two to three cyanate ester groups in one molecule, and more preferably has two cyanate ester groups, from the viewpoint of increasing the alignment of the molecular structure to easily improve thermal conductivity and to easily lower the melting point.
[0037] The cyanate ester curing agent preferably has a skeleton containing an aromatic ring, and more preferably has a skeleton containing a phenyl ring. By having a skeleton containing an aromatic ring, the alignment after curing is improved, and the thermal conductivity after curing is more likely to be improved. In addition, the cyanate ester curing agent preferably has a cyanate ester group directly bonded to the aromatic ring, and more preferably directly bonded to the phenyl ring. By directly bonding the cyanate ester group to the aromatic ring, the reactivity of the cyanate ester group is easily increased, and trimerization and curing are easily promoted by heating.
[0038] The molecular weight of the cyanate ester curing agent is preferably 500 or less. By having a molecular weight of 500 or less, the curing reaction with the resin is easily progressed, and it is easy to obtain a resin sheet with excellent thermal conductivity. In addition, the melting point of the cyanate ester curing agent is easily made to be equal to or less than a certain level, which improves the sheet property of the resin sheet and makes it easy to prevent cracks from occurring when the resin sheet is wound into a roll, for example. The molecular weight of the cyanate ester curing agent is more preferably 400 or less, and even more preferably 320 or less. In addition, the molecular weight of the cyanate ester curing agent is not particularly limited, but may be, for example, 150 or more, or may be 200 or more.
[0039] The cyanate ester-based curing agent may be a bisphenol-type cyanate ester. The bisphenol-type cyanate ester may have a structure in which a cyanate ester group is directly bonded to each phenyl group of the bisphenol skeleton. Examples of the bisphenol-type cyanate ester resin include bisphenol A-type cyanate ester resin, bisphenol E-type cyanate ester resin, and bisphenol F-type cyanate ester resin, and among these, bisphenol E-type cyanate ester resin is preferred. In addition, the cyanate ester-based curing agent may be a trimerized product (trimerized cyanate ester) of a part or all of the above bisphenol-type cyanate ester, but from the viewpoint of lowering the molecular weight and melting point, a monomeric bisphenol-type cyanate ester is preferred. The cyanate ester curing agent may be used alone or in combination of two or more kinds. As the cyanate ester-based curing agent, commercially available products can be used, such as "P-201" manufactured by Mitsubishi Gas Chemical Company, Inc., and "BA-230S", "BA-3000S", "BTP-1000S", and "BTP-6020S" manufactured by Lonza Japan Ltd.
[0040] <Diamine-based hardener> The diamine-based curing agent may be, for example, a compound having two amino groups. Here, the amino group may be either a primary amino group or a secondary amino group, but from the viewpoint of reactivity, a primary amino group is preferable. Therefore, it is preferable that the amine-based curing agent has two primary amino groups. As the diamine-based curing agent, from the viewpoint of improving the thermal conductivity by enhancing the alignment, an aromatic compound or an alicyclic compound can be mentioned, and from the viewpoint of reactivity and further improving the thermal conductivity by enhancing the alignment, an aromatic compound is preferable. The aromatic compound may be an aromatic compound having an aromatic ring, preferably a phenyl group, in the molecule. Specifically, it may be an aromatic amine in which an amino group is directly bonded to an aromatic ring, such as m-phenylenediamine, p-phenylenediamine, tolylene-2,4-diamine, tolylene-2,6-diamine, mesitylene-2,4-diamine, mesitylene-2,6-diamine, 3,5-diethyltolylene-2,4-diamine, 3,5-diethyltolylene-2,6-diamine, biphenylenediamine, 4,4-diaminodiphenylmethane, 2,5-naphthylenediamine, or 2,6-naphthylenediamine, or an amine in which an amino group is not directly bonded to an aromatic ring, such as m-xylylenediamine, p-xylylenediamine, or a reaction product of m-xylylenediamine and styrene. Among these, aromatic amines in which an amino group is directly bonded to an aromatic ring are more preferred from the viewpoint of reactivity. Examples of the alicyclic compound include alicyclic polyamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, cyclohexanediamine, methylcyclohexanediamine, isophoronediamine, and 4,4'-methylenebis(N-sec-butylcyclohexaneamine). The diamine curing agent may be used alone or in combination of two or more kinds.
[0041] The molecular weight of the diamine curing agent is preferably 500 or less, more preferably 300 or less, and even more preferably 250 or less. By making the molecular weight of the diamine curing agent below the upper limit, the amount of the curing agent present is reduced, and the amount of the resin present is increased, making it easier to obtain a resin sheet with excellent thermal conductivity. The molecular weight of the diamine curing agent is not particularly limited, but may be, for example, 100 or more, preferably 150 or more, and more preferably 170 or more.
[0042] <Acid anhydride curing agent> Examples of acid anhydride curing agents include phthalic anhydride, hexahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, 4-methyltetrahydrophthalic anhydride, and tetrabromophthalic anhydride. The acid anhydride curing agent may be used alone or in combination of two or more kinds.
[0043] The content of the curing agent is preferably 10 parts by mass or more and 150 parts by mass or less, more preferably 15 parts by mass or more and 120 parts by mass or less, and even more preferably 20 parts by mass or more and 110 parts by mass or less, relative to 100 parts by mass of the resin. When the content of the curing agent is equal to or more than the lower limit, the curing reaction with the resin proceeds sufficiently, and it is easy to obtain a resin sheet with excellent sheetability. When the content of the curing agent is equal to or less than the upper limit, the curing reaction with the resin can proceed without excessively containing the curing agent, and it is easy to suppress bleeding out of the curing agent. In addition, by increasing the amount of resin present as a result, it is easy to obtain a resin sheet with excellent thermal conductivity.
[0044] When the resin sheet contains an epoxy resin and a curing agent, the ratio of the equivalent of the curing agent to the equivalent of the epoxy resin (equivalent of curing agent / equivalent of epoxy resin) is not particularly limited, but is, for example, 0.3 or more and 2 or less, preferably 0.4 or more and 1.5 or less, and more preferably 0.5 or more and 1.2 or less.
[0045] (Cure accelerator) The resin sheet of the present invention may contain a curing accelerator. By containing a curing accelerator, the curing property of the resin sheet can be improved. The curing accelerator is not particularly limited, and examples thereof include imidazole-based curing accelerators, organic phosphine-based curing accelerators, and tertiary amine-based curing accelerators. Among them, it is preferable to use at least one selected from imidazole-based curing accelerators and organic phosphine-based curing accelerators.
[0046] Examples of imidazole-based curing accelerators include 1-cyanoethyl-2-phenylimidazole in which the 1-position of imidazole is protected with a cyanoethyl group, imidazole-based curing accelerators in which basicity is protected with isocyanuric acid, etc. Examples of commercially available products include 2MA-OK, 2MZ, 2MZ-P, 2PZ, 2PZ-PW, 2P4MZ, C11Z-CNS, 2PZ-CN, 2PZ-CNS, 2PZCNS-PW, 2MZ-A, 2MZA-PW, C11Z-A, 2E4MZ-A, 2MAOK-PW, 2PZ-OK, 2MZ-OK, 2PHZ, 2PHZ-PW, 2P4MHZ, 2P4MHZ-PW, 2E4MZ·BIS, VT, VT-OK, MAVT, MAVT-OK (all manufactured by Shikoku Chemical Industry Co., Ltd.).
[0047] Examples of organic phosphine curing accelerators include triphenylphosphine, tetraphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tri-tert-butylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, triphenylphosphine triphenylborane, etc. Examples of commercially available products include TPP, TPP-MK, TPP-K, TTBuP-K, TPP-SCN, TPP-S (all manufactured by Hokko Chemical Industry Co., Ltd.), etc.
[0048] The above curing accelerators may be used alone or in combination of two or more. The content of the curing accelerator is, for example, 0.3 parts by mass or more and 7 parts by mass or less, preferably 0.5 parts by mass or more and 5 parts by mass or less, and more preferably 0.7 parts by mass or more and 3 parts by mass or less, relative to 100 parts by volume of the total amount of the resin and the curing agent.
[0049] (Dispersant) The resin sheet of the present invention preferably contains a dispersant. The dispersant is blended in the resin together with the thermally conductive filler, etc., and improves the dispersibility of the thermally conductive filler, making it easier to suppress separation between the resin and the thermally conductive filler. As the dispersant, it is preferable to use a silane coupling agent. When using a silane coupling agent, it is preferable to surface treat the thermally conductive filler with the silane coupling agent, as described below. As the silane coupling agent, for example, an alkoxysilane compound can be used. The alkoxysilane compound is a compound having a structure in which, of the four bonds that a silicon atom (Si) has, 1 to 3 are bonded to an alkoxy group, and the remaining bonds are bonded to an organic substituent. The alkoxy group of the alkoxysilane compound is a hydrolyzable group, and examples thereof include a methoxy group, an ethoxy group, a protoxy group, a butoxy group, a pentoxy group, and a hexatoxy group. Among these, an alkoxysilane compound having a methoxy group or an ethoxy group is preferred. From the viewpoint of increasing the affinity with the thermally conductive filler, the number of alkoxy groups in the alkoxysilane compound is preferably 3. Therefore, the alkoxysilane compound is more preferably at least one selected from a trimethoxysilane compound and a triethoxysilane compound.
[0050] Examples of functional groups contained in the organic substituent of the alkoxysilane compound include an acryloyl group, an alkyl group, a carboxyl group, a vinyl group, a methacryl group, an aromatic group, an amino group, an isocyanate group, an isocyanurate group, an epoxy group, a hydroxyl group, and a mercapto group. In addition, by appropriately selecting the functional group, compatibility with the resin can be improved. From such a viewpoint, for example, when the resin contains an epoxy resin, the functional group is preferably an epoxy group.
[0051] In addition, the alkoxysilane compound is preferably an alkylalkoxysilane compound having an alkyl group bonded to a silicon atom, from the viewpoint of increasing the compatibility with the resin and increasing the dispersibility of the thermally conductive filler. The number of carbon atoms in the alkyl group bonded to the silicon atom is preferably 4 or more. In addition, the number of carbon atoms in the alkyl group bonded to the silicon atom is preferably 16 or less, from the viewpoint of keeping the viscosity of the resin composition low, since the viscosity of the alkoxysilane compound itself is relatively low. The alkoxysilane compound may be a polymeric silane compound having a polyorganosiloxane skeleton and an alkoxysilyl group.
[0052] Preferred alkylalkoxysilane compounds include n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, and n-decyltrimethoxysilane. Further, examples of alkoxysilane compounds other than alkylalkoxysilane compounds include 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and 3-phenylaminopropyltrimethoxysilane.
[0053] As the dispersant, a dispersant other than a silane coupling agent may be used. As the dispersant other than a silane coupling agent, for example, a polymeric dispersant other than a silicone compound may be used. As the polymeric dispersant used, a polymeric compound having a functional group may be used. As the polymeric compound, for example, an acrylic, vinyl, polyester, polyurethane, polyether, epoxy, polystyrene, amino, etc. may be used. In addition, as the functional group, for example, a carboxyl group, a phosphoric acid group, a sulfonic acid group, a carboxylate group, a phosphoric acid ester group, a sulfonic acid ester group, a hydroxyl group, an amino group, a quaternary ammonium base, an amide group, etc. may be used.
[0054] As the dispersant other than the silane coupling agent, a commercially available product may be used. For example, Phosphanol (registered trademark) RA-600, ML-200, ML-220, RS-610, RB-410, RD-720N (all manufactured by Toho Chemical Industry Co., Ltd.), Solsperse (registered trademark) SOLSPERSE26000, SOLSPERSE36000, SOLSPERSE41000 (all manufactured by ZENECA), "DISPERBYK "(registered trademark)-110, 111, 142, 145, 180, "BYK" (registered trademark)-110, 111, W969, W9010 (all manufactured by BYK Japan), Plysurf (registered trademark) A-208B, A-208F, A-208N, A-219B, DB-01, M208F (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), Disparlon (registered trademark) PW-36, DA-375 (all manufactured by Kusumoto Chemicals Co., Ltd.), and the like can be used.
[0055] The content of the dispersant in the resin sheet is not particularly limited, but is, for example, 0.5% by mass or more and 15% by mass or less, preferably 1% by mass or more and 10% by mass or less, and more preferably 2% by mass or more and 5% by mass or less, based on the total amount of components of the resin sheet excluding the thermally conductive filler. As the dispersant, the above-mentioned may be used alone or in combination of two or more kinds.
[0056] In the above description, when the thermally conductive filler is surface-treated with a silane coupling agent, the embodiment is shown in which the thermally conductive filler is surface-treated with the silane coupling agent blended in the resin, but the thermally conductive filler may be surface-treated with a silane coupling agent in advance and then mixed with the resin. By surface-treating the thermally conductive filler in advance with a silane coupling agent, the thermally conductive filler is surface-modified in advance with the silane coupling agent, and separation from the resin is easily suppressed. The thermally conductive filler that has been surface-modified in advance may be mixed with the resin to produce a resin composition.
[0057] The method of pre-treating the surface with a silane coupling agent is not particularly limited and may be a known method, for example, a wet treatment method, a dry treatment method, etc. In the wet treatment method, for example, a thermally conductive filler is added and mixed in a treatment liquid in which a dispersant is dispersed or dissolved in a solvent, and then the silane coupling agent is bonded or attached to the surface of the thermally conductive filler by drying, heating, washing, etc. The dry treatment method is a surface treatment method without using a solvent. Specifically, the thermally conductive filler is mixed with a dispersant and stirred in a mixer or the like, and then the mixture is heated to bond or adhere a silane coupling agent to the surface of the thermally conductive filler.
[0058] [Other ingredients] In addition to the above components, the resin sheet of the present invention may contain other additives such as a flame retardant, an antioxidant, a tackifier, a plasticizer, a thixotropy imparting agent, and a colorant. A solvent may be blended into the resin sheet in the manufacturing method thereof, and it is preferable that the blended solvent partly remains in the resin sheet.
[0059] The resin sheet of the present invention may be in an uncured or semi-cured state. When the resin sheet is in an uncured or semi-cured state, the resin sheet has high adhesion to another member and can be adhered to another member with high adhesive strength.
[0060] Thickness The thickness of the resin sheet is not particularly limited, but is, for example, 10 μm or more and 500 μm or less. If the thickness is 10 μm or more, a certain level of heat dissipation can be ensured, and if the thickness is 500 μm or less, electronic devices to which the resin sheet is applied, such as circuit boards and semiconductor devices, can be easily thinned, and the resin sheet can be particularly suitably used for component-embedded board applications. The thickness of the resin sheet is preferably 15 μm or more, more preferably 20 μm or more, and preferably 400 μm or less, more preferably 260 μm or less.
[0061] [Thermal Conductivity] The thermal conductivity of the resin sheet is preferably 0.2 W / (m·K) or more. When the thermal conductivity is 0.2 W / (m·K) or more, the heat dissipation is good. In addition, from the viewpoint of heat dissipation, the thermal conductivity is more preferably 0.3 W / (m·K) or more, and further preferably 0.5 W / (m·K) or more. As described above, when the thermal conductivity is increased, the heat dissipation is excellent, and when used as a circuit board or a board with built-in components, the heat generated by the electronic components mounted on the circuit board or the electronic components embedded inside the resin sheet can be efficiently released to the outside. In addition, the upper limit of the thermal conductivity of the resin sheet is not particularly limited, but in practical use, it is about 30 W / (m·K), for example. The thermal conductivity of the resin sheet can be determined as described in the examples described later.
[0062] [Laminate] The resin sheet of the present invention may be used in a laminate. The laminate may include a support and a resin sheet provided on the support.
[0063] Examples of the support include resin films made of plastic materials, metal foils, and release papers, with resin films made of plastic materials being preferred. When a resin film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0064] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0065] The surface of the support to be bonded to the resin sheet may be subjected to a matte treatment or a corona treatment. The support may be a support having a release layer on the surface to be bonded to the resin sheet. Examples of the release agent used in the release layer of the support having a release layer include one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins.
[0066] The thickness of the support is not particularly limited, but is, for example, in the range of 1 to 80 μm, preferably in the range of 5 to 75 μm, and more preferably in the range of 10 to 60 μm. When a support with a release layer is used, it is preferable that the thickness of the entire support with a release layer is in the above range.
[0067] In the resin sheet, a protective film can be further laminated on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The protective film can be the same as the support, and preferably a resin film can be used. By laminating the protective film, it is possible to prevent adhesion of dirt and the like to the surface of the resin composition layer and scratches. The resin sheet can be wound up in a roll and stored. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0068] [Resin composition] The resin composition according to the present invention contains a resin and a thermally conductive filler, and like the resin sheet, satisfies the following conditions (1) to (3). (1) The content of the thermally conductive filler is 50% by volume or more and 80% by volume or less based on the total volume of the resin composition. (2) The average particle size of the thermally conductive filler is 2 μm or more and 8 μm or less. (3) The thermally conductive filler contains a monocrystalline filler in an amount of 12% by volume or more based on the total amount of the thermally conductive filler.
[0069] The resin composition of the present invention may contain, in addition to the resin and the thermally conductive filler, other additives such as the above-mentioned curing agent, curing accelerator, dispersant, flame retardant, antioxidant, tackifier, plasticizer, thixotropy imparting agent, and colorant. The details of each component in the resin composition are as described in the resin sheet, and therefore detailed description thereof will be omitted. However, the contents of each component described based on the total amount of the resin sheet are based on the total amount of the resin composition in the resin composition.
[0070] (Method of manufacturing resin sheet and laminate) The resin sheet can be obtained by forming the resin composition into a sheet shape. The resin composition can be obtained by mixing various additives, such as a dispersant, a curing agent, a curing accelerator, and the like, which are optionally blended, in addition to the resin and the thermally conductive filler. The resin composition may also be diluted with a dilution solvent such as an organic solvent by adding the dilution solvent. Furthermore, the thermally conductive filler may be previously surface-treated with a surface treatment agent such as a silane coupling agent as described above, and then mixed with the resin.
[0071] The method of forming the resin composition into a sheet is not particularly limited, but for example, the resin composition may be coated or laminated on a release sheet, metal foil, or support, and dried by heating or the like as necessary to form a sheet. The term "sheet-like" or "sheet" refers to a thin, flat material whose thickness is small relative to its length and width, and the concept of a sheet also includes a material formed in the form of a film or layer on another member such as a support. As described above, a laminate can be obtained by forming a resin sheet on a support. Furthermore, the resin composition formed into a sheet (resin sheet) may be heated as necessary to be semi-cured into a B-stage state.
[0072] Examples of organic solvents used as dilution solvents include ketones such as acetone, methyl ethyl ketone (MEK) and cyclohexanone, acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate and carbitol acetate, carbitols such as cellosolve and butyl carbitol, aromatic hydrocarbons such as toluene and xylene, amide solvents such as dimethylformamide, dimethylacetamide (DMAc) and N-methylpyrrolidone, etc. The organic solvents may be used alone or in combination of two or more.
[0073] (How to use the resin sheet) The resin sheet may be cured and used as a cured product for various purposes. The resin sheet may be laminated in the uncured or semi-cured state on an adherend such as a metal base plate, other substrates, or electronic components, and cured to be adhered to the adherend. The resin sheet can be used in various applications requiring heat dissipation. That is, the present invention also provides a heat dissipation member formed from the resin sheet. In particular, it is preferably used as a heat dissipation member for electronic devices, and more preferably used in semiconductor devices.
[0074] More specifically, the resin sheet may be used as a part of a circuit board, or as an electronic component sealant for embedding electronic components composed of semiconductor chips or the like inside. Among these, it is preferable to use it as a sealant. The circuit board is preferably a component-embedded substrate. A component-embedded substrate generally has a narrow gap, and when a resin sheet is laminated in an uncured or semi-cured state, the resin tends to enter the narrow gap first, which tends to cause separation between the resin and the thermally conductive filler. However, the resin sheet of the present invention contains a predetermined amount of a thermally conductive filler having a relatively small average particle size, and is blended with a monocrystalline filler at a certain ratio or more, so that the separation is suppressed, and the resin sheet can be suitably applied to a component-embedded substrate having a narrow gap. The circuit board is preferably used for a semiconductor package. The semiconductor chip package includes a circuit board and a semiconductor chip mounted on the circuit board, and in the semiconductor chip package, the semiconductor chip is preferably sealed with the resin sheet of the present invention.
[0075] An example in which the resin sheet of the present invention is used in a semiconductor package is shown in Fig. 1. As shown in Fig. 1, for example, a semiconductor chip package 100 includes a semiconductor chip 110, an encapsulation layer 120 formed so as to cover the periphery of the semiconductor chip 110, and a resin layer 130 provided on the surface of the semiconductor chip 110 opposite to the side covered by the encapsulation layer, and the encapsulation layer 120 may be formed from the resin sheet of the present invention. The resin layer 130 may be, for example, an insulating layer, and may be formed from a known resin material or a thermally conductive resin composition. In the semiconductor package 100, the resin layer 130 may be provided with a conductive layer 140 that is electrically connected to the semiconductor chip 110, a solder resist layer 150, bumps 160 that are further connected to the conductive layer 140, and the like. However, the configuration of the semiconductor chip package shown in FIG. 1 is just an example, and specific examples of the semiconductor chip package are not limited to the configuration shown in FIG.
[0076] As described above, an example of a method for sealing electronic components such as semiconductor chips in a resin sheet using the resin sheet as a sealing material is as follows. The above-mentioned semiconductor chip package may be manufactured by the following method, but the manufacturing method of the semiconductor chip package is not limited to the following method. First, a fixing film to which an electronic component such as a semiconductor chip or an electronic component and a substrate is fixed is prepared. The fixing film may have an adhesive layer on one side, and the electronic component and the substrate may be fixed via the adhesive layer. Next, a resin sheet may be laminated on one side of the fixing film, and electronic components, or electronic components and a substrate, etc., may be embedded inside the resin sheet, and the resin sheet may be laminated on the fixing film. The resin sheet having electronic components, or electronic components and a substrate, etc. embedded therein as described above, is cured by heating to become a cured product, and electronic components such as semiconductor chips may be embedded inside and used as a component-embedded substrate. The resin sheet with the electronic components embedded therein as described above may be peeled off from the fixing film as appropriate, and other members (for example, the above-mentioned resin layer) may be formed on the surface from which the fixing film has been peeled off. The resin sheet may be cured after the fixing film has been peeled off, or may be cured on the fixing film. EXAMPLES
[0077] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0078] [Embeddability] As shown in FIG. 2, a 170 μm-thick resin sheet 10 obtained by the procedure shown in each of the Examples and Comparative Examples was laminated on a 75 μm-thick copper plate 12 having three φ10 μm through holes 11, and then pressed at 100° C. for 1 hour and then at 200° C. for 1 hour while maintaining a pressure of 1 MPa in a vacuum press to harden it. After curing was completed, the cross section of the through hole 11 was photographed by an optical microscope, and the image obtained by the photographing was analyzed by a dispersion degree measurement system ("Luzex AP" manufactured by Nireco Corporation) and evaluated as follows.
[0079] (Getting into a narrow space) The ability to get into narrow spaces was evaluated based on the following criteria. ⊚: The components of the resin sheet 10 flowed into all three through holes 11. ◯: Components of the resin sheet 10 flowed into two of the three through holes 11. Δ: The components of the resin sheet 10 flowed into one through hole 11 out of the three through holes. ×: The components of the resin sheet did not flow into any of the through holes 11. *Here, "flowed into the through hole" means that the components of the resin sheet flowed into the bottom of the through hole.
[0080] (Filler / resin separation) The probability (%) of the thermally conductive filler being present in regions 1 to 5 shown in FIG. 3 was calculated for each region by the above analysis, and the calculated probability of the thermally conductive filler being present was applied to the following formula (1) to calculate a value γ (%) for each region.
[0081]
number
[0082] Then, the filler / resin separation was evaluated based on the following evaluation criteria. ◯: γ was 3% or less in all regions. ×: There was one or more regions where γ exceeded 3%.
[0083] [Thermal Conductivity] The resin sheets obtained by the procedures shown in each of the Examples and Comparative Examples were cured by pressing them at 100° C. for 1 hour and then at 200° C. for 1 hour while maintaining a pressure of 1 MPa in a vacuum press. The thermal conductivity of the cured resin sheets in the thickness direction was measured using a laser flash thermal constant measuring device (NETZSCH "LFA447").
[0084] [Sheetability] As shown in FIG. 4, a resin sheet 10 having a width of 10 mm and a length of 100 m obtained by the procedure shown in each of the examples and comparative examples was wrapped around a metal rod 20 having a diameter of X mm, and the cracks were evaluated based on the following evaluation criteria. ⊚: When X was 3, no cracks occurred in the resin sheet. ◯: When X was 5, no cracks occurred in the resin sheet. ×: When X was 5 or more, cracks occurred in the resin sheet.
[0085] The components used in the examples and comparative examples are as follows.
[0086] (Thermal conductive filler) Alumina 1: "AA03", manufactured by Sumitomo Chemical Co., Ltd., average diameter 0.44 μm, single crystal α-alumina Alumina 2: "AA05", manufactured by Sumitomo Chemical Co., Ltd., average diameter 0.5 μm, single crystal α-alumina Alumina 3: "AA1.5", manufactured by Sumitomo Chemical Co., Ltd., average diameter 1.6 μm, single crystal α-alumina Alumina 4: "AA3", manufactured by Sumitomo Chemical Co., Ltd., average diameter 3.5 μm, single crystal α-alumina Alumina 5: "AA5", manufactured by Sumitomo Chemical Co., Ltd., average diameter 5.4 μm, single crystal α-alumina Alumina 6: "AA10", manufactured by Sumitomo Chemical Co., Ltd., average diameter 13.5 μm, single crystal α-alumina Alumina 7: "AS50", Showa Denko Co., Ltd., average diameter 9 μm, single crystal α-alumina Alumina 8: "Y2", manufactured by Ginet, average diameter 1.9 μm, crushed α-alumina Alumina 9: "Y4", manufactured by Ginet, average diameter 3.83 μm, crushed alpha alumina Alumina 10: "YC5", manufactured by Ginet, average diameter 6.25 μm, crushed α-alumina Alumina 11: "Y10", manufactured by Ginet, average diameter 11 μm, crushed α-alumina Alumina 12: "AO502", manufactured by Admatechs, average diameter 0.3 μm, polycrystalline θ alumina Alumina 13: "AO509", manufactured by Admatechs, average diameter 10.6 μm, polycrystalline θ-alumina Alumina 14: "DAW-01DC", manufactured by Denka, average diameter 1.6 μm, polycrystalline θ-alumina Alumina 15: "DAW-03DC", manufactured by Denka, average diameter 3.6 μm, polycrystalline θ alumina
[0087] Aluminum nitride 1: "HF-01D", Tokuyama Corporation, average diameter 1.3 μm, polycrystalline Aluminum nitride 2: "HF-10", Tokuyama Corporation, average diameter 7.8 μm, polycrystalline
[0088] Diamond 1: "AGD9", Tomei Diamond Co., Ltd., average diameter 9 μm, single crystal Diamond 2: "AGD11", Tomei Diamond Co., Ltd., average diameter 11 μm, single crystal
[0089] Silicon carbide 1: "SSC-A01", manufactured by Shinano Electric Smelting Co., Ltd., average diameter 1 μm, polycrystalline Silicon carbide 2: "SSC-A05", manufactured by Shinano Electric Smelting Co., Ltd., average diameter 5 μm, polycrystalline
[0090] (Epoxy resin) Epoxy resin 1: "JER828", Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 189g / eq Epoxy resin 2: "JER806", Mitsubishi Chemical Corporation, bisphenol F type epoxy resin, epoxy equivalent 165g / eq Epoxy resin 3: "YL6121HA", manufactured by Mitsubishi Chemical Corporation, an epoxy resin with a mesogenic structure, epoxy equivalent 175g / eq. Epoxy resin 4: "HP7200L", DIC, dicyclopentadiene type epoxy resin, epoxy equivalent 247g / eq
[0091] (hardening agent) Hardener 1: "P-201", manufactured by Mitsubishi Gas Chemical Co., Ltd., equivalent weight 132 Hardener 2: "TA", manufactured by Mitsubishi Gas Chemical Co., Ltd., equivalent weight 139 Hardener 3: "LA-1356", manufactured by DIC, equivalent weight 146 Hardener 4: "4,4-diaminodiphenylmethane", manufactured by TCI, equivalent weight 198 Hardener 5: "Rikacid MH-700", manufactured by New Japan Chemical Co., Ltd., equivalent weight 164
[0092] (polymer) Polymer 1: "JER1256", Mitsubishi Chemical Corporation, weight average molecular weight 50,000, phenoxy resin Polymer 2: "JER4250", Mitsubishi Chemical Corporation, weight average molecular weight 60,000, phenoxy resin Polymer 3: "JER4275", Mitsubishi Chemical Corporation, weight average molecular weight 60,000, phenoxy resin Polymer 4: "YX7553BH30", Mitsubishi Chemical Corporation, molecular weight 35,000, phenoxy resin Polymer 5: "YP-50S", Nippon Steel Chemical & Material Co., Ltd., molecular weight 50,000, phenoxy resin
[0093] (Cure accelerator) Curing accelerator 1: "2PHZ-PW", manufactured by Shikoku Chemical Industry Co., Ltd. Curing accelerator 2: "TPP-MK", manufactured by Hokko Chemical Co., Ltd.
[0094] (Dispersant) Dispersant 1: "KBM573", Shin-Etsu Chemical Co., Ltd., silane coupling agent Dispersant 2: "KBM403", Shin-Etsu Chemical Co., Ltd., silane coupling agent Dispersant 3: "KBM503", Shin-Etsu Chemical Co., Ltd., silane coupling agent Dispersant 4: "KBM3063", Shin-Etsu Chemical Co., Ltd., silane coupling agent Dispersant 5: "DISPER BYK111", manufactured by BYK Japan Dispersant 6: "DISPER BYK145", manufactured by BYK Japan
[0095] [Example 1] Each component shown in Table 1 and the solvent methyl ethyl ketone were added so that the solid content was 80 mass % to obtain a diluted resin composition. The diluted resin composition obtained was applied onto a support made of a release PET sheet and dried at 90°C for 10 minutes to form a thin film of the resin composition on the release PET sheet, thereby obtaining a resin sheet with a thickness of 100 μm.
[0096] [Examples 2 to 59, Comparative Examples 1 to 15] The same procedure as in Example 1 was carried out except that the formulation was changed as shown in Tables 1 to 8.
[0097] [Table 1]
[0098] [Table 2]
[0099] [Table 3]
[0100] [Table 4]
[0101] [Table 5]
[0102] [Table 6]
[0103] [Table 7]
[0104] [Table 8] *In Tables 1 to 8, the average particle size of the filler is the average particle size of all the thermally conductive fillers contained in the resin sheet.
[0105] As is clear from the above examples, a resin sheet satisfying the requirements of the present invention can penetrate into narrow spaces while suppressing separation of the resin and the thermally conductive filler, thereby exhibiting excellent thermal conductivity.
[0106] In contrast, the resin sheet produced in Comparative Example 1 had a lower filling rate of the thermally conductive filler than specified, which reduced the viscosity of the resin sheet and caused the resin to penetrate into the narrow spaces first, resulting in separation between the resin and the thermally conductive filler. The resin sheet produced in Comparative Example 2 was filled with an excessive amount of thermally conductive filler, which caused friction between the thermally conductive fillers and caused the thermally conductive fillers to lose their fluidity, resulting in separation between the resin and the thermally conductive fillers. In addition, the sheet properties were also deteriorated. The resin sheets produced in Comparative Examples 3 to 8 did not contain a single crystal filler, and therefore friction occurred between the thermally conductive fillers, causing separation between the resin and the thermally conductive fillers. In the resin sheets produced in Comparative Examples 9 and 10, the average particle size of the thermally conductive filler was smaller than the specified value, and therefore the surface area of the thermally conductive filler was increased, causing friction between the thermally conductive fillers and separation between the resin and the thermally conductive filler. Furthermore, in the resin sheets produced in Comparative Examples 10 to 15, the average particle size of the thermally conductive filler was larger than the specified value, so the thermally conductive filler could not penetrate into narrow spaces, and separation occurred between the resin and the thermally conductive filler. [Explanation of symbols]
[0107] 100 Semiconductor chip package 110 Semiconductor Chip 120 Sealing layer 130 Rewiring formation layer (insulating layer) 140 Conductor layer (rewiring layer) 150 Solder resist layer 160 Bump 10 Resin sheet 11 Through hole 12 Copper plate 1~5 areas 20 metal rod
Claims
1. A resin sheet comprising a resin and a thermally conductive filler, The resin sheet satisfies the following conditions (1) to (3). (1) The content of the thermally conductive filler is 50% by volume or more and 80% by volume or less based on the total volume of the resin sheet. (2) The average particle size of the thermally conductive filler is 2 μm or more and 8 μm or less. (3) The thermally conductive filler contains a single crystal filler in an amount of 12 volume % or more based on the total volume of the thermally conductive filler.
2. The resin sheet according to claim 1 , wherein the resin is a thermosetting resin.
3. The resin sheet according to claim 2 , wherein the thermosetting resin comprises an epoxy resin.
4. The resin sheet according to any one of claims 1 to 3, wherein the monocrystalline filler contains alpha alumina.
5. The resin sheet according to any one of claims 1 to 3, wherein the thermally conductive filler is surface-treated with a silane coupling agent, or the resin sheet contains a dispersant.
6. A heat dissipation member formed from the resin sheet according to any one of claims 1 to 3.
7. A laminate comprising a support and the resin sheet according to any one of claims 1 to 3 provided on the support.
8. A resin composition comprising a resin and a thermally conductive filler, The resin composition satisfies the following conditions (1) to (3). (1) The content of the thermally conductive filler is 50% by volume or more and 80% by volume or less based on the total volume of the resin composition. (2) The average particle size of the thermally conductive filler is 2 μm or more and 8 μm or less. (3) The thermally conductive filler contains a single crystal filler in an amount of 12 volume % or more based on the total volume of the thermally conductive filler.
Citation Information
Patent Citations
JP1974020929A
JP1974066221A
Pseudo waveform generating circuit
JP1989005209A
Epoxy resin composition and underfill material
JP2022060084A
Insulating curable composition , cured product thereof, and printed wiring board using same
WO2007020793A1